The Fund's Income Position for FY2007 : Midyear Review. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
In March and April this year, Executive Directors had wide-ranging discussions on the Fund's income outlook, which has changed significantly following the recent sharp decline in credit outstanding. Directors supported the proposal for a two-pronged strategy that would involve, first, immediate steps to address the projected income shortfall in FY2007 under current policies and within the framework of the FY2007 budget and, second, development of a broader work plan on the options to ensure a stable and sustainable income base.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United States